The effect of electrical stimulation in improving muscle tone (Clinical) - Azman, Muhammad Farhan; Azman, Amelia Wong (IOP Publishing, 2017)
Electrical stimulation (ES) and also known as neuromuscular electrical stimulation (NMES) and transcutaneous electrical stimulation (TES) involves the use of electrical current to stimulate the nerves or nerve endings that innervate muscle beneath the skin. Electrical stimulation may be applied superficially on the skin (transcutaneously) or directly into a muscle or muscles (intramuscularly) for the primary purpose of enhancing muscle function. The basic theoretical premise is that if the peripheral nerve can be stimulated, the resulting excitation impulse will be transmitted along the nerve to the motor endplates in the muscle, producing a muscle contraction. In this work, the effect of mere electrical stimulation to the muscle bulk and strength are tested. This paper explains how electrical stimulation can affect the muscle bulk, muscle size, muscle tone, muscle atrophy and muscle strength. The experiment and data collection are performed on 5 subjects and the results obtained are analyzed. This research aims to understand the full potential of electrical stimulation and identifying its possible benefits or disadvantages to the muscle properties. The results indicated that electrical stimulation alone able to improve muscle properties but with certain limits and precautions which might be useful in rehabilitation programme.